2016
DOI: 10.6061/clinics/2016(06)10
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smoking and smoking cessation on nasal mucociliary clearance, mucus properties and inflammation

Abstract: OBJECTIVE:The aim of the present study was to assess nasal mucociliary clearance, mucus properties and inflammation in smokers and subjects enrolled in a Smoking Cessation Program (referred to as quitters).METHOD:A total of 33 subjects with a median (IQR) smoking history of 34 (20-58) pack years were examined for nasal mucociliary clearance using a saccharine transit test, mucus properties using contact angle and sneeze clearability tests, and quantification of inflammatory and epithelial cells, IL-6 and IL-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 42 publications
1
54
0
2
Order By: Relevance
“…35 The improvement of NMC due to smoking cessation is caused by normalization of the cilia structure, genesis, and also ciliary beating function; changes of the cytomorphological features, such as fewer columnar cells, less mucus and reduced epithelial-cell metaplasia; restoration of the ionic transport function and mucus hydration at the basolateral membrane (increased mucus clearability); and detoxification of hydrogen peroxide through the activity of the glutathione peroxidase (antioxidant enxyme). 11,31 The finding of increased NMC value in passive smokers indicates that passive smokers present impairment of the NMC just like active smokers. 7,29,38 It has been observed that chronic passive exposure to cigarette smoke in the household has slightly higher serum continine, which is a metabolite of nicotine that decreases ciliary activity.…”
Section: Xavier Et Al 2013 20mentioning
confidence: 96%
See 1 more Smart Citation
“…35 The improvement of NMC due to smoking cessation is caused by normalization of the cilia structure, genesis, and also ciliary beating function; changes of the cytomorphological features, such as fewer columnar cells, less mucus and reduced epithelial-cell metaplasia; restoration of the ionic transport function and mucus hydration at the basolateral membrane (increased mucus clearability); and detoxification of hydrogen peroxide through the activity of the glutathione peroxidase (antioxidant enxyme). 11,31 The finding of increased NMC value in passive smokers indicates that passive smokers present impairment of the NMC just like active smokers. 7,29,38 It has been observed that chronic passive exposure to cigarette smoke in the household has slightly higher serum continine, which is a metabolite of nicotine that decreases ciliary activity.…”
Section: Xavier Et Al 2013 20mentioning
confidence: 96%
“…2,[8][9][10] Smoking is a significant risk factor for respiratory diseases, considering its ability to lead to an alteration of nasal mucociliary clearance (NMC). 2,11,12 Nasal mucociliary clearance is the primary innate defense mechanism of the nose and paranasal sinuses, and it consists of mucous layer, airway surface liquid layer, and ciliary epithelia. 2,[13][14][15] Mucus produced by the goblet cells of the mucosa is required for binding of the airborne pathogens (such as inhaled microbes and irritans).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, while the expelling of cigarette irritants through mucosal ciliature in smokers is inefficient, cigarettes induce coughing that enables the clearing process. In ex-smokers, it can take a year for the cilia to recover after cessation, during which ex-smokers can be susceptible to chest infections [36]. Whether the same mechanism has a role in Anisakis sensitization still remains to be tested.…”
Section: Risk Factors For Anisakis Sensitization In Fish Processing Wmentioning
confidence: 99%
“…Имеются сведе ния, свидетельствующие о негативных последстви ях курения для организма. Однако до настоящего времени не изучено воздействие табачного дыма на НЦ [15].…”
unclassified